2014
DOI: 10.1017/s1352465813001227
|View full text |Cite
|
Sign up to set email alerts
|

IAPT and Long Term Medical Conditions: What Can We Offer?

Abstract: It is concluded that it may be possible to modify a generic Step 2 IAPT intervention to demonstrate improvements both in terms of psychological wellbeing and self-management of T2DM. The main adaptations were related to more targeted recruitment and linking of diabetes specifically into the CBT model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…demonstrated that nurse‐led cognitive behaviour therapy interventions were effective, in older adults, in reducing distress about diabetes, and showed significant differences in glycaemic control after nine months. However, results were significant only for higher‐educated people, and interventions were run by nurses with expertise in diabetes …”
Section: Discussionmentioning
confidence: 96%
“…demonstrated that nurse‐led cognitive behaviour therapy interventions were effective, in older adults, in reducing distress about diabetes, and showed significant differences in glycaemic control after nine months. However, results were significant only for higher‐educated people, and interventions were run by nurses with expertise in diabetes …”
Section: Discussionmentioning
confidence: 96%
“…Consistent with recommendations by Wroe et al (2015), some therapists suggested that a range of health care professionals should be available for consultation to help understand the patient's physical state so best support them. Therapists were keen to receive basic medical information about patients.…”
Section: The Need For Specialized Servicesmentioning
confidence: 94%
“…Studies of treatment interventions using standard CBT protocols for depression and/ or anxiety in LTCs report low levels of engagement with these interventions (Ciechanowski et al 2010;Coventry et al 2015). Patients state that traditional CBT treatments fail to take into account the challenges of their illness (Hind et al 2010;Wroe et al 2015). Indeed, greater improvements in mood and quality of life outcomes are observed in primary care mental health treatment settings when standard CBT treatment principles are integrated alongside LTC self-management demands compared with CBT treatment approaches that provide no integration (De Lusignan et al 2015).…”
Section: B I O D a T Amentioning
confidence: 99%
“…; Wroe et al . ). Indeed, greater improvements in mood and quality of life outcomes are observed in primary care mental health treatment settings when standard CBT treatment principles are integrated alongside LTC self‐management demands compared with CBT treatment approaches that provide no integration (De Lusignan et al .…”
Section: Introductionmentioning
confidence: 97%